Neural correlates of fanhood: the role of fan identity and team brand strength - Cayolla, Ricardo; Biscaia, Rui; Baumeister, Roy F.; Chan, Hang-Yee; Duarte, Isabel C.; Castelo-Branco, Miguel (Frontiers in Human Neuroscience, 2024)
We analyzed the importance of fan identity and brand strength on fans' neural reactions to different team-related stimuli. A total of 53 fMRI scans with fans of two professional sport teams were conducted. Following up on a previous study we focused on the differences between fandom levels as well as the contrast between two team "brand" strength. Neural responses were compared among individuals based on their levels of fan identity. In sum, group comparisons between relatively high and lower identity and between weak and strong teams were made based on the notion that the latter reflects team brand strength (strong brand and weak brand). Findings indicate that brain activity in emotion regulation, memory, and cognitive control circuits is influenced by the relative level of fan identity. Higher-level identified fans showed increased reactivity to positive stimuli and the under-recruitment of their cognitive control circuits, suggesting more vulnerability to marketers' messages. The strength of the team brand activates different neural mechanisms. Neurally processed content depends on the relative brand's strength, highlighting the importance of brand-focused communications.